Investigating Teachers’ Conceptualizations of Deep Learning in Science Education - Nurwanti Fatnah; Zakiyyah; Mutiara Dwi Cahyani (Journal of Science Education Research, 2026)
This study investigates junior high school science teachers’ conceptualizations of deep learning within the context of Indonesian educational reform. Using a qualitative descriptive approach, data were collected from 39 science teachers in Cirebon through open-ended questionnaires and analyzed thematically using Atlas.ti. The results reveal that teachers define deep learning as a holistic process that integrates cognitive, affective, and psychomotor dimensions, emphasizing student-centeredness, collaboration, and meaningful learning. Teachers further articulated key principles of deep learning, including contextualization, critical and creative reasoning, innovation, independence, joyful and mindful learning, ethical awareness, and the ability to connect science concepts to real-life situations. The implementation of deep learning was characterized by project-based learning, authentic tasks, collaborative practices, backward design, and supportive classroom environments. However, teachers reported challenges such as limited resources, unequal technological access, time constraints, and diverse student readiness, indicating the complexity of translating deep learning into practice. To address these issues, teachers highlighted the need for systematic supports including sustained professional training, mentoring, peer observation, and high-quality instructional modules. The study contributes theoretically by clarifying teacher perspectives on deep learning and practically by offering recommendations for professional development and policy directions to strengthen deep learning in Indonesian science education.